Childhood Antecedents and Maintaining Factors in Maladaptive Daydreaming. Issue 6 (June 2016) - Somer, Eli; Somer, Liora; Jopp, Daniela S.
Abstract : Abstract: This study explored the fantasy activity of 16 individuals who were seeking online peer-support and advice for maladaptive daydreaming (MD). MD is an under-researched mental activity described as persistent vivid fantasy activity that replaces human interaction and/or interferes with important areas of functioning. We employed a grounded theory methodology that yielded seven common themes presented as a sequential descriptive narrative about the nature, precursors, and consequences of MD. The presented "storyline" included the following themes: (1) daydreaming as an innate talent for vivid fantasy; (2) daydreaming and social isolation—a two-way street; (3) the role of trauma in the development of MD; (4) the rewards of daydreaming; (5) the insatiable yearning for daydreaming; (6) shame and concealment; (7) unsuccessful treatment attempts. A main conclusion of our study is that there is an urgent need for early identification of MD and its correct diagnoses in adulthood.